Big: Teck New PREDATORY CAPITALISM: The tech giants are menacing democracy, privacy, and competition. Can they be housebroken? - DAYEN, DAVID (American Prospect)
The article offers information on how technology companies like Microsoft, Apple, and Facebook work at for-profit businesses, doing what for-profit businesses do in the U.S. which is to maximize shareholder profits by buying functional control of markets. The goal of these companies which is to make more money through more monopoly is emphasized.